(untitled) (Journal of EAHIL, 2016)
Micromedex is one of the most popular tools used by pharmacists to provide medicines information. This paper outlinesÂ a brief review of the product to determine whether it would be suitable for use by undergraduates in a particular UKÂ School of Pharmacy, that of UCL London.